(untitled) (SETARA : Jurnal Ilmu Hukum, 2024)
Legal facts show that corruption has occurred widely, massively, and structurally in Indonesia. This study examines the regulation of corruption crimes committed by active TNI members who hold civilian office and the authority of the Corruption Eradication Commission (KPK) in handling such crimes. This research uses a normative juridical method with statutory and conceptual approaches. The legal materials consist of primary and secondary legal materials. The study finds that KPK has authority to coordinate and handle corruption cases involving military personnel through the legal reasoning reflected in Article 65 paragraph (2) of the TNI Law and Article 42 of the KPK Law. However, jurisdictional tension remains between the KPK Law and the Military Justice Law. To minimize uncertainty, reform of the Military Justice Law and clearer affirmation of KPK authority are needed so that corruption law enforcement can be more effective.